The Universal Value of Islam as Rahmatan Lil 'Alamin - Abdulloh Safiq; M. Miftakhul Huda; Abdul Khamid (Indonesian Journal of Islamic Religion and Culture, 2024)
The scholars have determined that Islamic law has an eternal maqashid (goal) to preserve human intelligence, offspring, property, religion and self-esteem, because Islam never teaches enmity or hatred. This is where the term "religion that rahmatan lil alamin" is used to describe Islam. The research aims to complement existing studies and make Universal Islam an implementation of Rahmatan Lil 'Alamin. This research was carried out using a qualitative approach, and the researcher functioned as a key instrument, data collection methods were used qualitatively, data analysis was carried out inductively. Universal Islam contains teachings about Humanity (Al-Ihtimam Al-Insaniyah), Broad/Global Insight (Al-Ilmiah Al-Wasi'ah), High Integrity (Al-Nazaahah Al-Aliyah), Constantity and Flexibility (As-Tsawabit and Al —Mutaghayirat, Tolerance and Facilitation (Al-Samahah and Al-Taisir). Islam is universal and comprehensive, must be implemented in all dimensions of human life, including social and cultural life